Inheritance of resistance to fusarium wilt in pigeonpea (Cajanus cajan (L.) Millsp.) - Odeny, Damaris Achieng; Githiri, SM; Kimani, P.M. (2009)
The inheritance of resistance in pigeonpea (Cajanus cajan (L.) Millsp.) to fusarium wilt (Fusarium udum Butler) was studied in crosses between a resistant line ICP 8863 and two susceptible (ICP 2376 and LRG 30) pigeonpea lines. The parents, F1, F2 and backcross populations were screened for resistance to F. udum in a wilt-sick nursery at the ICRISAT Center. Resistance to fusarium wilt is controlled by a single recessive gene, which has been designated as pwr1.